Supplementary Figure 3 from A Single-Arm Phase Ib/II Study of Lenvatinib plus Eribulin in Advanced Liposarcoma and Leiomyosarcoma - Tom Wei-Wu Chen (15053003) (2025)
Changes of cell types based on (a) MCP-Counter and (b) Danaher module with post- vs pre-treatment samples. All tests were performed by non-parametric Wilcoxon test.